Risk Committees and Implied Cost of Equity Capital - Al-Hadi, Al-Hadi Ahmed; Hussain, S.; Al-Yahyaee, K.; Al-Jabri, H. (Wiley-Blackwell Publishing Asia, 2017)
© 2017 International Review of Finance Ltd. 2017. We investigate the association between the existence of risk committee and implied cost of equity capital in a unique institutional setting where the formation of the board risk committee as part of the risk governance mechanism is not mandatory in the Gulf Cooperation Council (GCC) financial institutions. Using data from the six GCC countries, we find that implied cost of equity capital is negatively associated with the existence of board risk committee. These findings indicate that GCC financial firms with better risk governance practices at board level have lower implied cost of equity capital. We contribute to the extant literature on-board risk governance in emerging market context.